Mine Closure : A Toolbox for Governments - World Bank (World Bank, Washington, DC, 2021)
The objective of this toolbox is to provide policy makers, governmental administrators, and lawmakers with the information needed to develop a broad governance framework that reduces the risks of an improperly managed mining industry and helps ensure successful mine closure. Every jurisdiction is unique and will require a solution that fits their legislative, cultural, economic and historical context. The toolbox is meant to provide examples of good international industry practice and basic legislative requirements that should be in place to facilitate closure. It also provides practical guidance and explanations for the key components of and process for developing a governance framework specific to mine closure. The tools found herein are based on GIIP including ICMM’s ‘Integrated Mine Closure: Good Practice Guide’, APEC’s ‘Mine Closure Checklist for Governments’, and other guidelines, frameworks, and standards. The ICMM and APEC publications include excellent information (e.g. checklists), which can be used in conjunction with this toolkit to guide the development of these frameworks. Section five sets out the legal elements that should be in place to facilitate closure, while sections six and seven highlight the socioeconomic and technical requirements of closure respectively. In each section guidance has been provided on key items that should be included in legislation, as well as suggested content to appear in policies and guidelines. Sections eight, nine, and eleven provide additional tools that are relevant for governments and other stakeholders in assessing and implementing closure practices. Section ten addresses some of the unique challenges that arise from legacy mines that were not closed in accordance with good international industry practice.